DANA PIHAK KETIGA DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA PADA PERBANKAN SYARIAH DI INDONESIA - Dewi Sartika (Signifikan: Jurnal Ilmu Ekonomi, 2013)
This study examines the effect of GDP (Gross Domestic Product) and the exchange rate on U.S. dollar against the TPF (Third Party Funds) in Indonesia. The objective of Islamic banking in this study was to analyze the influence of GDP (Gross Domestic Product) Rupiah rate against U.S. dollar deposits (Fund Party Third) of Islamic banking in Indonesia. In writing this makes the GDP (Gross Domestic Product) and the rupiah rate to U.S. dollar as the variables that influence to measure how much influence on Deposits (Third Party Funds). This study used 24 samples comprising the financial statements starting from January 2004 till December 2009. The method used in this study is the statistical method with a multiple regression model, where to find or measure how much influence given by the GDP (Gross Domestic Product) and exchange rate on U.S. dollar against the TPF (Third Party Funds) Islamic banking. The result showed that the variables GDP (Gross Domestic Product) and the exchange rate on U.S. dollar deposits have a significant effect on the Fund (Third Party) Islamic banking in IndonesiaDOI: 10.15408/sjie.v2i2.2426